ANALISIS FRAMING PEMBERITAAN POLITIK PADA MEDIA LOKAL “SAMARINDA BERADAB” - Rosya Amalia; Harmonis (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze political news framing in the local media “Samarinda Beradab,” particularly regarding the performance of the Mayor of Samarinda. The media generally presents neutral reporting but tends to emphasize positive aspects of government performance. This raises concerns about the construction of a favorable public image. This research uses a qualitative approach through literature study and content analysis of Instagram and Facebook posts. The findings indicate that the media framing consistently portrays leadership as responsive, solution-oriented, and proactive. Additionally, there is an indication of positive bias characterized by dominant government perspectives, minimal criticism, and consistently positive narratives, even in potentially negative issues. Therefore, “Samarinda Beradab” functions more as a government communication tool rather than a fully balanced media outlet.